Routing in networks using genetic algorithm. (2018) - Moza, Meenakshi; Kumar, Suresh
With the recent increase in the traffic, internet service providers are forced to seek solutions for better and improved services within the available resources. While the current traffic loads have to be taken into account for computation of paths in routing protocols, network applications require the shortest paths to be used for a speedy communication. The open shortest path first (OSPF) is the routing algorithm used to find the shortest path from source to destination, however, the overloading of the path or link congestion exposes the limitations of OSPF. This shortcoming can be overcome by optimisation of the network through the application of genetic algorithm, as it provides a valuable alternative to the overloaded path between the source and the destination. This paper proposes a distinct method of calculating the shortest path in a network by extending OSPF algorithm with genetic algorithm (OSGA) for achieving the desired improved performance.